A Survey on Multipath Routing Protocol for Wireless Sensor Networks Based on Infrastructure - Jin, Yongxian; Zhu, Hong (IJRDO -Journal of Computer Science Engineering, 2016)
Abstract: With the development of science and technology of the times, the wireless sensornetwork has been inextricably linked with people's lives, the traditional ad hoc network has beeninsufficient to meet the needs of people in all aspects. Among them, the quality of the wirelesssensor network routing technology plays a vital role to achieve the success of using theapplications. In this paper, some infrastructure based multipath routing technologies for wirelesssensor network are studied deeply, and they are divided into three categories: energy-awaremultipath routing protocol, hierarchy based multipath routing protocol and ant based multipathrouting protocol. The current typical multipath routing protocols are classified, analyzed andcompared, and some new ideas for future research work are proposed.